A big little life ebook A memoir of a joyful dog named trixie. - Koontz, Dean (2011)
NEW YORK TIMES BESTSELLER • In a profound, funny, and beautifully rendered portrait of a beloved companion, bestselling novelist Dean Koontz remembers the golden retriever who changed his life. A retired service dog, Trixie was three when Dean and his wife, Gerda, welcomed her into their home. She was superbly trained, but her greatest gifts couldn’t be taught: her keen intelligence, her innate joy, and an uncanny knack for living in the moment. Whether chasing a tennis ball or protecting those she loved, Trixie gave all she had to everything she did, inspiring Dean and Gerda to trust their instincts and recapture a sense of wonder that will remain with them always. Trixie lived fewer than twelve years; in this wide world, she was a little thing. But in every way that mattered, she lived a big life.